CONTINUOUS AUDIT: TANTANGAN DALAM IMPLEMENTASI - Taufan Adi Kurniawan (Universitas Sarjanawiyata Tamansiswa, 2017)
The Purpose of this study is to identify challanges and barriers for continuous audit implementation in various countries, this study is using literature study methodology to identify based on continuous audit implementation in various countries such as Brazil, South Africa, and China. Although there is various challanges and barriers in various country but it can be concluded that the major challanges and barriers in continuous audit implementation is human, process, technology, and industrial environment.